Investigating The Problem-Based Learning Environment For Digital Visual Effects Education At Multimedia University - Ng, Lynn-Sze (2008)
This paper explores and reports the experience of implementing PBL as a teaching and learning strategy for the education of Digital Visual Effects (DVE). It provides an evaluation of both the teaching and learning processes, as well as documents the use of PBL in developing critical thinking and decision making skills, acquisition of knowledge base, fostering self directed learning, and promoting positive personal attitude and professionalism among students.